Recent Kinematic and Kinetic Advances in Olympic Alpine Skiing: Pyeongchang and Beyond - Supej, Matej; Holmberg, H.-C. (Frontiers in Physiology, 2019)
Alpine skiing has been an Olympic event since the first Winter Games, 1936. Nowadays, skiers compete in four main events: slalom, giantslalom, super-G and downhill. Here, we present an update on the biomechanics of alpine ski racers and their equipment. The technical and tactical ability of today’s world-class skiers have adapted substantially to changes in equipment, snow conditions and courses. The wide variety of terrain, slopes, gate setups and snow conditions involved in alpine skiing requires skiers to continuously adapt, alternating between carving and skidding turning techniques. The technical complexity places a premium on minimizing energy dissipation, employing strategies and ski equipment that minimize ski-snow friction and aerodynamic drag. Access to multiple split times along the racing course, in combination with analysis of the trajectory and speed provide information that can be utilized to enhance performance. Peak ground reaction forces, which can be as high as 5x body weight, serve as a measure of the external load on the skier/equipment. Although the biomechanics of alpine skiing have significantly improved, several questions concerning optimization of skiers’ performance remain to be investigated. Recent advances in sensor-technology that allow kinematics and kinetics to be monitored can provide detailed information about the biomechanical factors related to success in competitions. Moreover, collection of data during training and actual competitions will enhance the quality of guidelines for training future Olympic champions. At the same time, the need to individualize training and skiing equipment for each unique skier will motivate innovative scientific research for years to come